2007
DOI: 10.1007/s10646-007-0149-x
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal fungi and ectomycorrhiza associated bacteria isolated from an industrial desert soil protect pine seedlings against Cd(II) impact

Abstract: Effects of mycorrhization with Amanita rubescens or Hebeloma sinapizans and dual inoculation with the fungi and ectomycorrhiza associated bacteria (EMAB) Pseudomonas putida or Bacillus cereus on seedling growth and accumulation of Cd(II) in Pinus sylvestris were studied. Both fungal and bacterial species were isolated from roots of pines growing in an industrial area polluted with high concentrations of heavy metals. During mycorrhization, A. rubescens colonized higher number of pine seedlings than H. sinapiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 43 publications
2
19
0
3
Order By: Relevance
“…Por otro lado, se ha encontrado que las asociaciones tripartitas (hongo ectomicorrízico-bacterias asociadas-especie forestal) han resultado beneficiosas en suelos contaminados con metales pesados, ya que estudios recientes han demostrado que la colonización de plántulas del pino albar (Pinus sylvestris L.) con hongos ectomicorrízicos específicos y bacterias asociadas a éstos provee protección a la especie forestal contra el efecto de ciertos metales pesados como zinc, cadmio y plomo, siendo promisorio su uso para el establecimiento de plantaciones de coníferas en suelos contaminados con estos metales (Kozdrój et al 2007).…”
Section: Figuraunclassified
See 1 more Smart Citation
“…Por otro lado, se ha encontrado que las asociaciones tripartitas (hongo ectomicorrízico-bacterias asociadas-especie forestal) han resultado beneficiosas en suelos contaminados con metales pesados, ya que estudios recientes han demostrado que la colonización de plántulas del pino albar (Pinus sylvestris L.) con hongos ectomicorrízicos específicos y bacterias asociadas a éstos provee protección a la especie forestal contra el efecto de ciertos metales pesados como zinc, cadmio y plomo, siendo promisorio su uso para el establecimiento de plantaciones de coníferas en suelos contaminados con estos metales (Kozdrój et al 2007).…”
Section: Figuraunclassified
“…Sin embargo, es importante resaltar que la colonización bacterial de las ectomicorrizas muestra cierta especificidad entre el hospedero y el simbionte, pudiendo influenciar positiva o negativamente en la micorrización y por ende en el crecimiento de las plantas (Garbaye 1994, Poole et al 2001. Esta especificidad posiblemente está dada por el efecto combinado del tipo de suelo, el simbionte fúngico, la planta hospedero y la localización de las comunidades asociadas con las ectomicorrizas del árbol (Timonen et al 1999, Kozdrój et al 2007, haciendo entendible por qué no todas las bacterias inoculadas en P. patula colonizaron la raíz micorrizada o los diferentes niveles de micorrización encontrados. Por otro lado, Shishido et al (1996) encontraron que diferentes especies de Bacillus incrementan el crecimiento longitudinal de las coníferas por mecanismos diferentes a la micorrización.…”
Section: Figuraunclassified
“…From all research stations healthy fruiting bodies with dimensions of 10-14 cm in height and approx 5 cm cap diameter were harvested and pure cultures of mycelium were derived in accordance to tissue method developed by Pachlewski and modified by Kozdroj [11] what involves cutting in sterile condition sections of plectenchyma from the centre of the cap of approx. 0.5 cm width, length and thickness.…”
Section: Selection Of Mycorrhizal Fungi Speciesmentioning
confidence: 99%
“…This is well documented in wooden plants that go into the mutualistic mycorrhizal symbiosis and produce ectomycorrizal roots which preserve, store and exchange mineral salts and water [9]. It has been shown that this type of plant association with fungi significantly enhance their tolerance to toxic concentration of heavy metals in soil [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Pines inoculated with Laccaria bicolor while exposed to Cd grew better than non-mycorrhizal plants and maintained a higher nutrient status (Ahonen-Jonnarth and Finlay 2001), an effect that might be further strengthened by ectomycorrhiza associated bacteria (Kozdroj et al 2007). The beneficial effect induced by the fungus is nevertheless species and isolate specific.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%